2016
DOI: 10.1039/c6fo00288a
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan from Undaria pinnatifida prevents vascular dysfunction through PI3K/Akt/eNOS-dependent mechanisms in the l-NAME-induced hypertensive rat model

Abstract: Despite major scientific advances in its prevention, treatment and care, hypertension remains a serious condition that might lead to long-term complications such as heart disease and stroke. The great majority of forms of hypertension eventually result from an increased vasomotor tone activity that is regulated by endothelial NOS (eNOS) in vascular endothelium. Here, we examined the effect of fucoidan on eNOS activation in human umbilical vein endothelial cells (HUVECs). We also examined the effects of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 78 publications
3
22
0
Order By: Relevance
“…Nitric oxide, an important pro-inflammatory mediator, is mainly synthesized by iNOS enzyme which would excessive express in reaction to various immune and inflammatory stimuli. The excessively produced NO could result in the generation of various pro-inflammatory mediators and cytokines, which would further promote the development of inflammation and finally relate to tissue damage and detrimental inflammatory disorders [40]. The high level of iNOS is often accompanied with over-expressed COX-2 in the inflammatory process, and COX-2 is the key enzyme required for the conversion of arachidonic acid into PGE2 which is a characteristic marker of inflammatory damage [7].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide, an important pro-inflammatory mediator, is mainly synthesized by iNOS enzyme which would excessive express in reaction to various immune and inflammatory stimuli. The excessively produced NO could result in the generation of various pro-inflammatory mediators and cytokines, which would further promote the development of inflammation and finally relate to tissue damage and detrimental inflammatory disorders [40]. The high level of iNOS is often accompanied with over-expressed COX-2 in the inflammatory process, and COX-2 is the key enzyme required for the conversion of arachidonic acid into PGE2 which is a characteristic marker of inflammatory damage [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, NG-nitro-L-arginine methyl ester (L-NAME) was used to induce hypertension in mice. Oral administration of 100 mg/kg/day of fucoidan for 4 weeks in these animals decreased blood pressure and increased production of nitric oxide production ( 31 ). Notably, many of these in vivo studies were done in male rats and mice only and further research is needed to evaluate their efficacy in female animals.…”
Section: Fucoidanmentioning
confidence: 99%
“…AKT also plays a critical role in the control of phosphorylation of eNOS-ser1177 in vivo. Li et al [39] revealed that the upregulation of phosphorylated AKT and eNOS induced by fucoidan was counteracted by the suppression of AKT and eNOS phosphorylation protein expression. PI3K and AKT are downstream effectors of insulin signaling and are important signaling molecules in the regulation of glycogen metabolism in myocytes, lipocytes, and hepatocytes.…”
Section: The Role Of Each Specific Pathway Associated With Oxidatimentioning
confidence: 99%